Satellite-based cultivation scheduling for Eucheuma sp. using landsat-8 imagery in coastal aquaculture systems - Isnaeni A (Bioculture Journal, 2025)
Background: Seaweed cultivation in Jeneponto Regency has been practiced for a long time and has become the main livelihood for most people in Mallasoro Bay. In cultivating seaweed, obstacles often arise in the form of failure experienced by seaweed farmers or the quality of the harvest is not good. Methods: This study aims to develop a calendar for planting seaweed Eucheuma sp. in Mallasoro Bay, Jeneponto Regency based on sea surface temperature and chlorophyll-a distribution obtained from Landsat-8 imagery.  Findings: Processing of Sea Surface Temperature Imagery and Chlorophyll-a processed using ENVI 4.8 dan 5.3 software, satellite images used in clean conditions and no cloud disturbances. In this research, data analysis was carried out descriptively. The water temperature that is good for seaweed growth is 27-30°C, for the Mallasoro Bay Sea Surface Temperature, which is suitable for planting seaweed in April, May, June, July, August, September, October, and November. While the classification based on the criteria of chlorophyll-a trophic status in marine waters, namely the range < 1 mg/L is classified as Oligotrophic, 1-3 mg/L is classified as Mesotrophic, 3-5 mg/L is classified as Eutrophic, and > 5 mg/L is classified as hypertrophic. Conclusion: from the results of image analysis for the distribution of chlorophyll-a in Mallasoro Bay, it shows that Mallasoro Bay throughout the year is at the Mesotrophic level or the fertility level of the waters is quite fertile because it is in the range of 1-3 mg/L. so the seaweed planting calendar in Mallasoro Bay is obtained,  namely in January, February, and December, equipment preparation such as cleaning and repair of seaweed planting equipment can be carried out, then at the end of March, May, July, and September, the procurement of seaweed seeds is carried out , in early of April, June, August, and October, Novelty/Originality of this article: it is possible to spread seaweed seeds, then in mid of May,  July, September, and November, harvesting is carried out, so that seaweed cultivation in a year can be carried out 4 times cycle.